2015
DOI: 10.1080/13548506.2015.1034733
|View full text |Cite
|
Sign up to set email alerts
|

An online study combining the constructs from the theory of planned behaviour and protection motivation theory in predicting intention to test for chlamydia in two testing contexts

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. rachael.powell@manchester.ac.uk). Permanent repository link AcknowledgementsWe are grateful to our Google account manager Ram Vadlamani for his support in developing the keywords for the Google AdWords campaign. RP was funded by an RCUK Academic ResearchFellowship at Aston University. AbstractChlamydia is a common sexually-transmitted infection that has potentially serious consequences unless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As for smoking behavior, a series of studies revealed that perceived rewards of smoking, especially intrinsic rewards, were consistently positively related to smoking intentions and behavior, and self-efficacy to avoid smoking was negatively related to smoking [ 25 , 26 , 29 31 ]. Recently, Protection motivation was successfully applied for the prediction of preventing a group of infectious and chronic non-communicable diseases, such as HIV/AIDS [ 32 , 33 ], Chlamydia [ 34 ], Respiratory Infectious Disease [ 35 ], Coronary Artery Disease [ 36 ], Cervical Pap Test Practice [ 37 , 38 ] and other cancer prevention behaivors [ 39 – 43 ]. What’s more, tropical infectious diseases such as malaria, PMT has also been proved to be a powerful tool in analyzing malaria preventive behaviors [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for smoking behavior, a series of studies revealed that perceived rewards of smoking, especially intrinsic rewards, were consistently positively related to smoking intentions and behavior, and self-efficacy to avoid smoking was negatively related to smoking [ 25 , 26 , 29 31 ]. Recently, Protection motivation was successfully applied for the prediction of preventing a group of infectious and chronic non-communicable diseases, such as HIV/AIDS [ 32 , 33 ], Chlamydia [ 34 ], Respiratory Infectious Disease [ 35 ], Coronary Artery Disease [ 36 ], Cervical Pap Test Practice [ 37 , 38 ] and other cancer prevention behaivors [ 39 – 43 ]. What’s more, tropical infectious diseases such as malaria, PMT has also been proved to be a powerful tool in analyzing malaria preventive behaviors [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, confidence in performing the required behavior (i.e., self-efficacy) and the belief that this behavior will be effective in reducing or eliminating a health threat (i.e., response efficacy) enhance the intention to perform protective behaviors. Components of this theory (vulnerability, self-efficacy, and response efficacy) were found to be predictors of protective behaviors, including (self-)testing, for other infectious diseases, such as Chlamydia trachomatis (CT) and COVID-19 [ 23 , 24 ]. With regard to requesting discharged contact patients to participate in contact investigations for antibiotic-resistant bacteria, this theory highlights the importance of sending out carefully composed self-sampling request letters.…”
Section: Discussionmentioning
confidence: 99%
“…A more constructive approach might be for future studies to use methodologies that allow greater concealment of identity to facilitate this recruitment. We have recently successfully used on-line advertising and on-line questionnaires to ask people about self-testing in a quantitative study [ 35 ]. It may be that online methods of both advertising studies and interviewing participants may make it easier for private people with stigmatized conditions to take part, with a higher degree of anonymity.…”
Section: Discussionmentioning
confidence: 99%